Human Metapneumovirus: A Critical Review of Its Impact on the Immune System and Clinical Implications - Shahidul Islam, Syed Mahmood; Laskar, Nourjahan; Reza, Md.Shajalal; Ahmed, MD. Faisal; Iqbal, Hrishik; De Guia, Lemar Cardenas; Syrmos, Nikolaos (Utan Kayu Publishing, 2025)
Human Metapneumovirus (HMPV) became known in 2001 as a major respiratory pathogen which triggers acute respiratory tract infections (ARTIs) in the population with particular impact on infants and elderly patients and individuals with impaired immunity. HMPV was recently identified but retrospective analyses show this virus has existed unnoticed throughout previous decades starting from the 1950s. The respiratory tract pathogen HMPV exists within the Pneumoviridae family with genomic and structural relationships to respiratory syncytial virus (RSV). The virus manifests differently from delicate upper respiratory conditions to dangerous bronchiolitis and pneumonia within the lower respiratory system. Medical practitioners discover it difficult to identify HMPV due to identical viral symptoms but RT-PCR now enhances testing precision. HMPV has a seasonal pattern which reaches its peak during late winter and spring through airborne respiratory droplet transmission. Most people acquire the virus before their fifth year but continued infections happen as natural protection weakens so there remains an urgent need to develop safe treatments and vaccines against HMPV. FDA-approved antiviral drugs along with vaccines do not exist for treatment so healthcare professionals must provide supportive care only. Studies of HMPV's spread have improved yet scientists have not resolved fundamental questions about lineage immunity protection and virus immune evasion behaviors and persistent immune responses. The prevention of HMPV transmission requires proper hand hygiene practice together with respiratory etiquette. Multidisciplinary research needs continuous investigation because it helps tackle the worldwide burden of HMPV while developing specific prevention methods for this enduring public health threat that affects vulnerable populations.